Social capital, Chinese style: individualism, relational collectivism and the cultural embeddedness of the institutions-performance link - Carsten Herrmann-Pillath (Frankfurt School of Finance & Management, 2009)
China is the odd man out in the research on social capital and economic performance. A brief survey of recent World Values Survey data depicts China to be a high-trust, achievement oriented society, which does not fit into popular pictures of rampant corruption and abuses of power. I argue that one difficulty results from methodological issues in research on social capital, where a universally accepted theory of social capital is lacking, including theoretically grounded methods of measurement. These resulting applications often generalize a Western notion of civil society as a benchmark, implicitely. I propose that social capital has to be conveived as a context-bound intermediate level theoretical term, putting methodological arguments by Durlauf (economics) and Little (Chinese studies) together. The resulting empirical method is that of triangulation across different disciplines, combining emic and etic approaches. I present an application on the notorious phenomenon of guanxi in China, which results into their re-conceptualization as Ego-centric networking and relational collectivism, based on a culturally specific framing of affectual aspects of social relations. With this notion of culturally specific social capital, we can better understand the relation between institutions and economic performance in China.
urn:nbn:de:101:1-20091023793
Keywords: A12; O43; P39; Z13; 330; Social capital; China; guanxi; collectivism and individualism; culture and emotions